Strategy In Support Of Micro, Small And Medium Agro-Based - Fitra Ariansyah; Laode Asrul; Eymal, B. Demmallino (International Journal of Science, Technology & Management, 2021)
This study aims to identify and evaluate the factors including internal (strengths and weaknesses) and external scope (opportunities and threats) in determining the strategy of the Balai Diklat in support the growth of agro-based micro, small and medium enterprises in Makassar City, as well as to determine the Balai Diklat strategy with a deep SWOT analysis support the growth of small and medium agro-based enterprises in the City Area Makassar. Data collection techniques use observation, documentation, interview, with the analysis used is the SWOT analysis. Research result indicates that the factors comprising the internal environment with pay attention to the strengths and weaknesses and the external environment, namely opportunities and threats. Wherefrom the analysis of the internal and external environment hence the results of this study the Makassar Industrial Education and Training Center still has strength and great opportunities in overcoming weaknesses and threats. From the analysis of the results of strategy determination using SWOT analysis, including strategic planning, strategy determination, and decision-making stages regarding the strategy, the strategy carried out by BDI Makassar in encouraging the growth of agro-based micro, small and medium enterprises Develop competency-based training modules and curriculum, Implement monitoring and evaluating programs/activities, recruiting processing machine instructors, general graphic and functional design instructor, Organizing 3 in 1 training, competency-based industrial system training and business incubator, and Improve the quality of human resources by attending training, industrial apprenticeships and writing KTI.